(E)-1-(3-Formylphenyl)-2-(2-oxidonaphthalen-1-yl)diazen-1-ium - Assia Mili; Ali Benosmane; Mohamed Amine Benaouida; Abdelkader Bouchoul; Salah Eddine Bouaoud (Acta Crystallographica Section E, 2013)
In the title zwitterion, C17H12N2O2, the dihedral angle between the benzene ring and naphthalene ring system is 11.76 (7)° and an intramolecular N—H...O hydrogen bond exists. In the crystal, molecules are linked via pairs of C—H...O hydrogen bonds, forming inversion dimers.